Produção e índice nutricional de tifton 85 submetido a formas de parcelamento e doses de nitrogênio - Sonego, Etiane Tanise (2013)
The nitrogen fertilization is a determining factor of production in fodder species, such as Cynodon sp.Tifton 85. The aim of this work was to evaluate the effect of split application of nitrogen in daily rate of accumulation and the accumulated production of dry matter of Tifton 85, as well as the nutritional index of nitrogen, phosphorus and potassium; nitrogen dilution curve and the nitrate levels in soil. The experiment was conducted in the area of Instituto Agronômico do Paraná (IAPAR) experimental station of Pato Branco - PR, in experimental year 2011/12 and repeated in 2012/2013. The experimental design was randomized complete blocks with sub sub subdivided plots with four repetitions. The plots consisted of accumulated days of evaluation, the subplots had as treatment single doses of N and fertilizer splitting doses in two and four times, in sub-plots were allocated the doses of N (0, 100, 200, 300 Kg ha-1) and sub sub plots the sampling depths of soil (0-5, 5-10, 10-20 cm). The higher rate of accumulation obtained in the first year was 142 Kg of MS.ha-1. day-1 and in the second year was 105 Kg of MS.ha-1.day-1 being both influenced by splitting doses of nitrogen fertilization two and four times respectively. The production of MS in experimental first year was influenced by splitting the doses of N from the dose of 200 Kg N ha-1, being the largest production (15,134 Kg of MS.ha-1) observed in splitting into four times the dose of 300 kg N ha-1, which differed from the application in a single dose (12,485 Kg of MS.ha-1). In the second year the production of dry matter was influenced only by the doses of nitrogen, being the largest production MS of 16,092 Kg of MS.ha-1 obtained with the highest dose of N (300 Kg ha-1). The index nutritional N was unable to detect the deficiencies of N being the curve of dilution of N, more need for nutritional diagnosis. The Nutritional Index of phosphorus was not limiting the development of plants in both experimental years. In the second year the experimental rates of potassium were insufficient in fragmentation of once and twice. The levels of nitrate in soil for the first year were not influenced by experimental splitted applications of nitrogen fertilization even in the application of the highest dose of N, considering that in the second year, these were influenced by splitted applications of nitrogen fertilization. Therefore, for Tifton 85 established and with management of residual nitrogen fertilization of the previous year the parceling for doses up to 383 Kg of N ha-1 is unnecessary.